Comparative analysis of spatiotemporal trends in sea surface temperature in the major marine protected areas of the Eastern Tropical Pacific (Revista de Biología Marina y Oceanografía, 2023)
The Eastern Tropical Pacific (ETP) is characterized by complex oceanographic dynamics that affect the regional sea surface temperature (SST), a key parameter driving marine ecosystems. To date no comparative studies have been conducted on the spatial and temporal variations of SST among the several marine protected areas in the ETP. The present study used remote sensing to evaluate the monthly, annual, and decadal variations in SST from 1982 to 2019 in Coiba National Park (Coiba), Cocos Island National Park (Cocos), Malpelo Fauna and Flora Sanctuary (Malpelo), Gorgona Island National Park (Gorgona), Galápagos Marine Reserve (Galápagos) and La Plata Island (La Plata). An overall increasing trend in SST was observed across all study sites, except for West Galápagos. A decrease in SST anomaly was observed from February through April at Malpelo, Coiba, Gorgona and La Plata. These observations are likely in response to the Humboldt Current and upwelling events in the Colombian Pacific Basin. Using a longer SST dataset is recommended to determine if the annual, monthly and decadal trends observed here are driven by local, regional or global processes. Consistent monitoring of SST trends is a strategic practice in understanding and planning for current and projected changes in the marine environment.